Existential risk analysis and the future of employability - Romero Vela, Sonia Lidia (2020)
Humanity is in danger of extinction, the world lives a war against an invisible enemy in the 21st century, the Covid-19 pandemic, which not only puts people's lives at risk, but also shows us the inhuman side to which the neoliberal policy has led us such as: the abandonment of health, education, and security. The main objective of this research is to analyze existential risk and employability. Bibliographic review was carried out, as well as the analysis of documents, decrees, norms and laws. Artificial intelligence, biotechnology and the pandemic itself were identified as potential existential risks for the future work. It is necessary to reflect from a public policy that considers the future of employability at existential risk facing the covid-19 and post-pandemic context.